Substantial decline of polychlorinated biphenyls serum levels 10 years after public health interventions in a population living near a contaminated site in Northern Italy. (October 2016) - Magoni, Michele; Donato, Francesco; Speziani, Fabrizio; Leonardi, Lucia; Orizio, Grazia; Scarcella, Carmelo; Gaia, Alice; Apostoli, Pietro
Abstract: Introduction: Polychlorinated biphenyls (PCBs) are persistent pollutants classified among endocrine disruptors and human carcinogens. In an urban area in Northern Italy (Brescia), a chemical factory producing PCBs from 1938 to 1984 caused soil and food pollution. Since the discovering of the environmental pollution in the area in 2001, various public health interventions have been implemented to avoid human contamination. Methods: Two independent surveys were carried out in 2003 and 2013 using the same study design and methods. A random sample of the adult general population living in four areas of the town with different soil contamination level was enrolled in both surveys. Investigation included serum levels of 24 PCB congeners and of other common clinical-chemical parameters and questions about residential and occupational history as well as current and past diet and consumption of locally produced food. 537 subjects were tested in the 2003 and 488 in the 2013 survey. Results: Total PCB serum levels showed a strong correlation with age (Spearman r = 0.71 in 2003 and r = 0.80 in 2013), but not with gender. Consumers of food produced in the most polluted area had higher total PCB serum levels (median 15.6 and 4.7 ng/ml in 2003 and 2013, respectively) than non-consumers (4.1 and 2.3 ng/ml) and consumers of food produced in non-polluted areas (6.5 and 1.9 ng/ml), with increasing trend of PCB serum levels with cumulative local food intake. PCB serum levels from 2003 to 2013 survey declined by around half in all age groups, especially among the youngest people. The total PCB reduction was found to be due to a combination of a birth cohort effect (− 41% every 10 years) and survey period effect (− 18% in 2013 versus 2003), with medium chlorinated CB congeners showing the most relevant reduction (− 30%) between the two surveys. High chlorinated CBs were more strongly associated with birth cohort (− 46% every 10 years): in the 2013 survey they represented 58% of total PCBs in 60–79 years old while they were 37% among the under 40s with a median value 20 times higher in the oldest than in the youngest (3.1 versus 0.16 ng/ml). Conclusions: PCBs serum levels declined from the 2003 to 2013 survey though they are still high in the elderly mainly because of past intake of locally produced contaminated food. Present findings suggest that PCBs food chain contamination and human absorption have been interrupted successfully in the area since discovery of the pollution in 2001. Highlights: PCBs serum levels have declined by around half in a decade. Intake of food produced in polluted areas was the main source of human contamination. Public health measures have interrupted food chain contamination. PCB decline was associated with birth cohort and survey period.